Changes of Plasma Amino Acid Profiles in Infants With a Nutrient-Fortified Complementary Food Supplement: Evidence From a 12-Month Single-Blind Cluster-Randomized Controlled Trial - Furuta, Chie; Sato, Wataru; Murakami, Hitoshi; Suri, Devika J.; Otoo, Gloria E.; Tano-Debrah, Kwaku; Ghosh, Shibani A. (Frontiers in Nutrition, 2021)
Stunting is reportedly associated with low circulating levels of essential amino acids (EAAs). This study examined the effect of a macronutrient- and micronutrient-fortified complementary food supplement (KOKO Plus) on specific plasma EAA levels and stunting in infants aged 6-18 months. In a single-blind cluster-randomized controlled trial conducted in Ghana, infants were enrolled at 6 months and followed until 18 months. Thirty-eight communities were randomly assigned to receive KOKO Plus (KP, fourteen communities, n=321), multiple-micronutrient powder (MN, thirteen communities, n=327), or only nutritional education as control group (NE, eleven communities, n=318), and all groups received nutrition education. Plasma amino acids (AAs) were measured at 6, 12, and 18 months (end point). Mixed-effects models were used to assess the effect of the intervention on plasma AAs, and the relationship between plasma branched-chain AAs (BCAAs) and the risk of stunting was assessed. At the end point, total BCAA concentrations (± standard error) significantly exceeded baseline in the KP (284.2 ± 4.3 µM) and NE (289.1 ± 4.4 µM) groups but not the MN group (264.4 ± 4.1 µM at 200 sachets). After adjustment for compliance at 200 sachets, plasma BCAAs exceeded in the KP group (284.5 ± 4.2 µM) compared to the MN group (264.6 ± 4 µM). Plasma BCAAs were positively correlated with changes in length-for-age Z-score from baseline (R = 0.327, p = 0.048). In conclusion, the plasma BCAA concentrations of infants that received KP and the NE group was significantly higher compared to the MN group but there were no differences between the KP and NE group at end point. Improved plasma BCAAs may be due to improved nutrient intake by infants exposed to KP or NE. Low BCAAs were associated with stunting, replicating the previous finding. This trial was registered on ClinicalTrials.gov as NCT03181178 (https://clinicaltrials.gov/ct2/show/NCT03181178?term=NCT03181178&draw=2&rank=1).